Investigação da enzima NAD(P)H quinona desidrogenase 1 (NQO1) recombinante como alvo molecular da naftoquinona RCDFC na ação citotóxica contra células de câncer de pulmão - Costa, Pedro Mikael da Silva (2024)
Accumulation of mutations and epigenetic modifications in neoplastic cells confers characteristics such as sustained signaling for proliferation, resistance to cell death and metabolic reprogramming. Due to the pro-oxidative state, one of the strategies that tumor cells use to resist reactive oxygen species increasing is the expression of antioxidant enzymes, such as NAD(P)H-Quinone Oxidoreductase 1 (NQO1). The enzyme NQO1 catalyzes the conversion of quinones to semiquinones, protecting the cell against oxidative stress, and is overexpressed in solid tumors such as lung, breast and prostate cancer. This study sought to understand the interaction between NQO1 protein and the naphthoquinone RCDFC. Recombinant NQO1 protein was produced using Escherichia coli as expression platform, purified by IMAC followed by SEC and characterized by SDS-PAGE and DLS. The NQO1-RCDFC interaction was evaluated by end-point enzyme assay, NADH consumption monitoring assay, differential scanning fluorimetry, evaluation of intrinsic tryptophan fluorescence and secondary structure evaluation using circular dichroism. Protein crystallography tests were also started. The antineoplastic effect of RCDFC was investigated using the MTT assay, evaluation of cell morphology, membrane integrity, cell viability, cell cycle, ROS formation, and expression of DNMTs. It was also assessed whether RCDFC causes erythrocyte hemolysis. The NQO1 protein was obtained with a yield of 1 mg/L of culture and 80% monodisperse. It was shown that RCDFC inhibits the enzymatic activity of NQO1, decreases NADH consumption, increases Tm, alters conformation of secondary structures and modifies tryptophans chemical environment. The Kd value of RCDFC interacting with NQO1 was estimated at 0.28 μM, lower than the Kd of the control ligand dicumarol (0.48 μM). The MTT assay showed that RCDFC has antineoplastic effect on solid tumor cell lines and hematological tumors. RCDFC has been shown to cause chromatin condensation, loss of cytoplasmic content, cell volume shrinkage and cytoplasmic vacuolization in A549 lung cancer cells. In these cells, RCDFC exerts a cytostatic effect with cell cycle arrest in the G1 and S phases, accumulation of ROS and reduction of DNMT1 and DNMT2 gene expression. RCDFC showed low hemolytic potential in mouse erythrocytes. The inhibition of NQO1 by the naphthoquinone RCDFC appears to be a promising strategy for target-directed pharmacological therapy in the fight against lung cancer.